Alkali metals association in biomass and their impact on ash melting behaviour. (1st February 2020) - Mlonka-Mędrala, Agata; Magdziarz, Aneta; Gajek, Marcin; Nowińska, Katarzyna; Nowak, Wojciech
Highlights: Agriculture residues and energy crops mineral matter properties were investigated. Potassium in the ash was detected as KCl, K2 SO4, K2 CO3 and K3 PO4 . K, Ca, Mg are the main reactive elements in the biomass ashes. Eutectic mixtures have a strong influence on ash melting behaviour. A new model was proposed to predict the alkali compounds concentration. Abstract: Selected agricultural and energy crop biomass ashes represented by two mixed cereal straws, corn straw, Miscanthus × Gigantus and Salix Viminalis were chosen for ash behaviour investigation and prediction of operating problems during biomass combustion. The presence of aggressive species in the ash generate operational problems of heat exchanging surfaces in power boilers connected with slagging and fouling processes, limiting the use of biomass direct combustion for energy production. In this work, thermal behaviour characteristics, transformation properties of the inorganic components and ash fusion temperatures of biomass ashes were investigated using thermal analysis (STA), X-ray diffraction (XRD) and high-temperature microscope. The special attention was focused on the evaluation of potassium compounds presented in ashes. Potassium was detected as KCl, K2 SO4, K2 CO3 and K3 PO4 . It was noted, that presence and concentration of alkali metals, silicon and calcium compounds has the major impact on fusion temperatures of studied ashes. Leaching process of ash elements using water, ammonium acetate and hydrochloric acid solutions was performed to determine the association of alkali metals in the raw material. Based on the results, a mineral matter composition recalculation model was proposed to predict alkali compounds concentration in the fuel. The model might be also used to determine the risk of eutectics formation, which have the strongest influence on ash melting behaviour.